Redefining Da'wah Management Graduate Competencies in Islamic State Universities - Sugiharto, Guruh (International Journal Of Education, Social Studies, And Management (IJESSM), 2024)
This study aims to provide a redefinition of the competence of da'wah management graduates. These competencies are rearranged based on the work needs in Hajj and Umrah travel companies. The results of this study indicate that these competencies can be explained through the MTEC model, namely Managerial, Technology, Ethics, and Communication. With this competence, the education and employment sectors can link and match. Thus increasing the absorption of graduates in the job market and making it easier for companies to get quality human resources.